Ensino e performance musical em rede: soluções open source para a prática instrumental e vocal remotos - Silva, Merlia Helen Faustino da (2023)
The knowledge, development and use of technological tools as a support for musical performance and teaching activities are increasingly necessary, both for the optimization of performance preparation processes and for the geographic expansion and democratization of music teaching. In this work we will address the possibilities of networked music in teaching and musical performances, presenting Jack and JackTrip software as free solutions. In the development of the artifact following the DSR methodology, a systematic survey of the literature on network music and the use of JackTrip was carried out, with which we were able to identify the classes of problems and how the creation of the artifact would be relevant to the community involved. In order to validate the artifact, we carried out instruction and practical tests of the Jack and JackTrip tools with geographically distributed musicians and music teachers, having a 100MB home network as the main server. With real-time communication, it is possible for the teacher to play exercises and listen to the student synchronously, perform collective rehearsals between voices and instruments and have a real perception of the sound made by the student in terms of dynamics and other points of performance.